Analyzing English's Impact on Global Competitiveness and Sustainable Progress - Marliana, Rini (Lembaga Riset Mutiara Akbar, 2024)
The objective of this research is to conduct a thorough analysis of the role of English as a catalyst for progress, with a particular emphasis on its impact on global competitiveness and sustainable development. The research methodology involves a library research approach, which entails a comprehensive analysis of a wide range of relevant literature sources, including scholarly journal articles, books, research reports, and policy documents related to English, global competitiveness, and sustainable development. The data obtained from these sources were then subjected to a qualitative analysis to identify patterns of relationships and arguments for or against the role of English as a catalyst for progress in the context of global competitiveness and sustainable development. The results of the study indicate that English language acquisition significantly contributes to improving global competitiveness by facilitating access to information, employment opportunities, and international collaboration. Furthermore, the study found that English plays an important role in knowledge and technology transfer, which is crucial for innovation and sustainable development. These findings underscore the importance of continued investment in quality and equitable English language education as a strategy to enhance global competitiveness and achieve sustainable development goals. This research provides theoretical foundations and insights for policymakers and practitioners.